Structure, Process and Outcome Evaluation of Central Public Health Laboratory Performance About Neonatal Screening Program in Karbala in 2022 - Dunia Fawaz Mohammed; Mahdi Murshd Thuwaini; Alaa Hussein Abed (University of Thi-Qar Journal of Science, 2023)
Background: Neonatal screening is a preventive medical act aims to early detecting neonates affected byspecific disorders that endanger their lives or cause long-term health problems and require prompt intervention. This canresult in significant reductions in morbidity, death, and related costs and disabilities. The panel of neonatal screened disordershas been gradually expanded. Expansion has been empowered with the introduction of tandem mass spectrometry, whichallowed for the screening of up to 40–50 diseases with a single blood spot. Part of the implementation of neonatal screeningprogram must include, just like any other program, monitoring and evaluation task in order to identify difficultiesor barriers to improve procedures and methodologies. This study aimed to evaluate the Central Public Health Laboratory/Karbala Directorate of Health performance in Neonatal Screening program. Method: The evaluation method has beencarried out in Holy Karbala Governorate for the period between the first of September 2021 and the end of June 2022using a check list of standards taken from the National Guideline for Newborn Screening for Care Providers inPrimary Health Care Centers in Iraq. This was to evaluateCentral Public Health Laboratory by meeting the manager employee and evaluate theCentral Public Health Laboratory room.